Before the coffee gets cold - Kawaguchi, Toshikazu, 1971-; Trousselot, Geoffrey (London : Picador, an imprint of Pan Macmillan, 2019)
c
Originally published in Japan as Coffee ga samenai uchini by Sunmark Publishing Inc., Tokyo, Japan in 2015.
Keywords: Coffeehouses -- Japan -- Tokyo -- Fiction; Time travel -- Fiction; Interpersonal relations -- Fiction